Method for preparing a positive electrode active material for a rechargeable lithium-ion battery

JP7634548B2Active Publication Date: 2025-02-21UMICORE(BE)
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2022549346
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-05-14
Filing Date
2021-02-17
Publication Date
2025-02-21
Estimated Expiration
2041-02-17

Smart Images

  • Figure 0007634548000015
    Figure 0007634548000015
  • Figure 0007634548000016
    Figure 0007634548000016
  • Figure 0007634548000017
    Figure 0007634548000017
Patent Text Reader

Abstract

1. A powdered positive electrode active material for a lithium-ion secondary battery, the powdered positive electrode active material having particles comprising Li, M, and O, the particles having a Li / M molar ratio of 0.98 or more and 1.10 or less, the powder being characterized in that the powder has a flowability of at least 0.10 and a maximum of 0.30 when the powder has a D50 of at least 4.0 μm and a maximum of 6.0 μm, or a flowability of at least 0.10 and a maximum of 0.20 when the powder has a D50 of more than 6.0 μm and a maximum of 10.0 μm, wherein D50 is the median particle size of the powder.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a process for preparing a powdered positive electrode active material for a lithium ion secondary battery. [Background technology]

[0002] The present invention relates to a process for preparing a powdered positive electrode active material for a lithium ion secondary battery. The powdered positive electrode active material has particles containing Li, M, and O, where M is: Co with a content x of 5.0 mol% or more and 40.00 mol% or less; Mn with a content y of 5.0 mol% or more and 40.00 mol% or less; A having a content c of 0.01 mol% or more and 2.00 mol% or less, containing at least one element from the group consisting of at least one element of W, Al, and Si; D with a content z of 0 mol% or more and 2.00 mol% or less, containing at least one element from the group consisting of Mg, Al, Nb, Zr, B, W, and Ti; and It consists of Ni with a content of (100-xycz) mol%.

[0003] The particles have a Li / M molar ratio of 0.98 or more and 1.10 or less.

[0004] Specifically, the powdered positive electrode active material is represented by the general formula: Li a Ni 1-x-y-c-z Co x Mn y D z O d and comprising particles containing at least one oxide of A, A being present in the powder in an amount of 0.01 mol % or more and 2.00 mol % or less, and 0.98≦a≦1.10, 0.05≦x≦0.40, 0.00≦y≦0.40, 0.00≦z≦0.02, and 1.80≦d≦2.20.

[0005] The process is Preparing a first powder mixture comprising a lithium source, a nickel source, a cobalt source, a manganese source, and optionally a source of D; sintering the powder mixture at a temperature of at least 300°C and at most 1000°C to obtain an agglomerated sintered body; The method includes a step of pulverizing the aggregated sintered body to obtain the powdered positive electrode active material.

[0006] In the framework of the present invention, a step of sintering a powder by a heat treatment process is applied to produce an agglomerated sintered body. The agglomerated sintered body is thus a product resulting from said sintering process, having an agglomerated shape comprising particles that come together to form clusters of particles having a given median size. Said clusters can be broken down into powders having a median size smaller than that of the agglomerated sintered body.

[0007] Such a process for preparing such a powdered positive electrode active material is already known, for example from WO 2019 / 185349 (hereinafter referred to as WO'349).

[0008] The disadvantage of the process according to WO'349 is that the throughput of the step of grinding the agglomerated sintered body to obtain a powdered positive electrode active material is low. This grinding step is essential because it converts the agglomerated sintered body into a powdered positive electrode active material as an intermediate product, which can be further processed to obtain a final powdered positive electrode active material product, or breaks down the agglomerated clusters of particles that constitute the final powdered positive electrode active material product to meet the target particle size and its specific distribution. Furthermore, a molding step is required to incorporate the final powdered positive electrode active material product into the cathode, which is optimized when the powder does not agglomerate in the slurry dispersion.

[0009] This low throughput associated with the poor flowability of the powdered positive electrode active material ultimately translates into a low production rate (i.e., a low ratio between the amount of powdered positive electrode active material produced and the time spent producing it).

[0010] It should be noted that fluidity usually cannot be improved by more thorough grinding. On the contrary, finer powders typically have worse fluidity than coarser ones, or else they are similar powders.

[0011] In fact, low fluidity causes a bottleneck effect that reduces the capacity of the entire manufacturing process of the positive electrode material. The consequence of having a bottleneck in the manufacturing process leads to production stagnation, excessive procurement inventory, and pressure from customers.

[0012] Therefore, there is a need to currently design a powdery positive electrode active material with improved and controlled fluidity, thereby realizing a process for manufacturing the powdery positive electrode active material with higher throughput.

[0013] A powdery positive electrode active material with improved fluidity is defined with D50 as the median particle size of the powdery positive electrode active material (and expressed in μm), and measured, for example, according to the method described in Section 1.4. It should be understood that it is a powdery positive electrode active material having a flowability FI such that 0.10 ≤ FI ≤ 0.30 when 4.0 μm ≤ D50 ≤ 6.0 μm, or 0.10 ≤ FI ≤ 0.225 when 6.0 μm < D50 ≤ 10.0 μm.

[0014] The positive electrode active material is defined as a material that is electrochemically active in the positive electrode. It should be understood that the active material is a substance that can capture and release Li ions when exposed to voltage changes over a predetermined period of time.

[0015] In this document, fluidity is measured with a 6-inch diameter annular shear cell having a volume of 230 cm 3 and is defined as the slope of a straight line fitted by the least squares method to the experimental results of the uniaxial fracture strength measured at several major consolidation stresses.

[0016] The fluidity is measured using a Brookfield PFT powder flow tester, a well-known and powerful instrument for measuring the fluidity of powders, with the standard software provided by the manufacturer and using the torsional speed of one rotation per hour and the axial speed of 1 mm / sec, which are the standard settings of this software.

Summary of the Invention

Means for Solving the Problems

[0017] The purpose of designing a powdery positive electrode active material having a fluidity FI of 0.10 ≦ FI ≦ 0.30 when 4.0 μm ≦ D50 ≦ 6.0 μm or 0.10 ≦ FI ≦ 0.20 when 6.0 μm < D50 ≦ 10.0 μm, with D50 defined as the median particle size of the powdery positive electrode active material, is achieved by providing the process according to claim 1. By the process according to claim 1, the fluidity of the powdery positive electrode active material produced therefrom can be controlled.

[0018] In fact, as shown in the results of Table 9, it is observed that the fluidity of the powdery positive electrode active materials obtained from the processes according to EX1, EX2, and EX3.1 is improved. In fact, the powdery positive electrode active materials according to EX1.1, EX1.2, EX2.1, EX2.2, EX3.1, and EX3.2 show fluidity values of ≦ 0.30 when 4.0 μm ≦ D50 ≦ 6.0 μm and ≦ 0.20 when 6.0 μm < D50 ≦ 10.0 μm.

[0019] The present invention relates to the following embodiments.

[0020] Embodiment 1 In a first aspect, the present invention relates to a process for producing a powdery positive electrode active material for a lithium-ion secondary battery having particles containing Li, M, and O, where M is Co with a content x of 5.0 mol% or more and 40.00 mol% or less, Mn with a content y of 5.0 mol% or more and 40.00 mol% or less, A having a content c of 0.01 mol% or more and 2.00 mol% or less, containing at least one element from the group consisting of at least one element of W, Al, and Si; D with a content z of 0 mol% or more and 2.00 mol% or less, containing at least one element from the group consisting of Mg, Al, Nb, Zr, B, W, and Ti; (100-xycz) mol% Ni content, the particles having a Li / M molar ratio of 0.98 or greater and 1.10 or less, and the process comprises Preparing a powder mixture comprising a lithium source, a nickel source, a cobalt source, a manganese source, and optionally a D source; sintering the powder mixture at a temperature of at least 300°C and at most 1000°C to obtain an agglomerated sintered body; The method includes grinding the agglomerated sintered body to obtain a powdered positive electrode active material, the method being characterized in that a source of at least one of W, Al, and Si is ground together with the agglomerated sintered body.

[0021] Optionally, the process described in embodiment 1 is characterized in that a source of any one of the elements W, Al, or Si is milled together with the agglomerated sintered body.

[0022] Preferably, the powdered positive electrode active material has a median particle size D50 of at least 4.0 μm and at most 10.0 μm, more preferably at most 9.0 μm, even more preferably at most 8.0 μm.

[0023] Preferably, the step of breaking down the agglomerated calcined body is carried out in an air classifying mill.

[0024] For the sake of completeness, it is noted that in this document the source of at least one of the elements W, Al and Si refers to a source external to the agglomerated sintered body.

[0025] EMBODIMENT 2 In a second embodiment, preferably as described in embodiment 1, the source of A is a nanometer-sized oxide powder.

[0026] By nanometer sized powder is meant a powder having a median particle size of less than 1.0 μm and greater than or equal to 1.0 nm.

[0027] EMBODIMENT 3 In a third embodiment, preferably as described in embodiment 1 or 2, the aluminum source is Al2O3.

[0028] EMBODIMENT 4 In a fourth embodiment, preferably as described in embodiment 1 or 2, the silicon source is SiO2.

[0029] EMBODIMENT 5 In a fifth embodiment, preferably as described in any one of the first to fourth embodiments, the tungsten source is WO3.

[0030] EMBODIMENT 6 In a sixth embodiment, which is preferably described in any one of the first to fifth embodiments, the Ni-based precursor is at least one compound selected from the group consisting of a Ni-based oxide, a Ni-based hydroxide, a Ni-based carbonate, or a Ni-based oxyhydroxide.

[0031] EMBODIMENT 7 In a seventh embodiment, as preferably described in any of the first to sixth embodiments, the lithium source is at least one compound selected from the group consisting of Li2CO3, Li2CO3·H2O, LiOH, LiOH·H2O or Li2O.

[0032] EMBODIMENT 8 In an eighth embodiment, preferably as described in any one of the third to seventh embodiments, an aluminum source is added in the grinding step so that the molar content of aluminum is 0.08 mol % or more and 1.50 mol % or less relative to the sum of the molar contents of Ni, Mn, and Co in the agglomerated sintered body.

[0033] EMBODIMENT 9 In the ninth embodiment, preferably as described in any one of Embodiments 4 to 7, a silicon source is added in the pulverization step in a molar content of silicon of 0.36 mol% or more and 1.45 mol% or less with respect to the total molar content of Ni, Mn, and Co in the aggregated fired body.

[0034] Embodiment 10 In the tenth embodiment, preferably as described in any one of Embodiments 5 to 7, a tungsten source is added in the pulverization step so that the molar content of tungsten is 0.20 mol% or more and 0.35 mol% or less with respect to the total of the molar contents of Ni, Mn, and Co in the aggregated fired body.

[0035] Embodiment 11 In a second aspect, the present invention includes a powdery positive electrode active material for a lithium ion secondary battery having particles containing Li, M, and O, where M is Co with a content x of 5.0 mol% or more and 40.00 mol% or less, Mn with a content y of 5.0 mol% or more and 40.00 mol% or less, A with a content c of 0.01 mol% or more and 2.00 mol% or less, containing at least one element from the group consisting of W, Al, and Si, containing at least one element from the group consisting of Mg, Al, Nb, Zr, B, W, and Ti, D with a content z of 0 mol% or more and 2.00 mol% or less, and consisting of Ni with a content of (100 - x - y - c - z) mol%, the particles have a Li / M molar ratio of 0.98 or more and 1.10 or less, and the powdery positive electrode active material has a fluidity FI of 0.10 ≤ FI ≤ 0.30 when the powder has 4.0 ≤ D50 ≤ 6.0, or 0.10 ≤ FI ≤ 0.225 when 6.0 < D50 ≤ 10.0, where D50 is defined as the median particle size in micrometers (μm).

[0036] Preferably, D50 is at least 4.0 μm and at most 10.0 μm, more preferably at most 9.0 μm, and even more preferably at most 8.0 μm.

[0037] Preferably, when 6.0 < D50 ≤ 8.0, 0.10 ≤ FI ≤ 0.20.

[0038] The fluidity of the powdery positive electrode according to the second aspect of the present invention is at least 0.10 and at most 0.30.

[0039] The FI of the powder in the solid state is acceptably at least 0.10. Powders having an FI lower than 0.10 are liquid and thus flow uncontrollably fast.

[0040] In an optional embodiment, the fluidity FI of the powder described in Embodiment 11 is when 4.5 μm ≤ D50 ≤ 6.0 μm, 0.10 ≤ FI ≤ 0.30, or when 4.0 μm ≤ D50 ≤ 5.0 μm, 0.10 ≤ FI ≤ 0.30, or when 4.5 μm ≤ D50 ≤ 5.0 μm, 0.10 ≤ FI ≤ 0.30, or when 4.0 μm ≤ D50 ≤ 6.0 μm, 0.15 ≤ FI ≤ 0.30, or when 4.0 μm ≤ D50 ≤ 6.0 μm, 0.20 ≤ FI ≤ 0.30, or when 4.0 μm ≤ D50 ≤ 6.0 μm, 0.10 ≤ FI ≤ 0.25, or when 4.0 μm ≤ D50 ≤ 6.0 μm, 0.15 ≤ FI ≤ 0.25, or when 4.5 μm ≤ D50 ≤ 6.0 μm, 0.15 ≤ FI ≤ 0.30, or when 4.5 μm ≤ D50 ≤ 5.5 μm, 0.15 ≤ FI ≤ 0.25, or when 6.0 μm < D50 ≤ 8.0 μm, 0.10 ≤ FI ≤ 0.20, or when 6.0 μm < D50 ≤ 8.0 μm, 0.15 ≤ FI ≤ 0.20, or when 7.0 μm < D50 ≤ 8.0 μm, 0.10 ≤ FI ≤ 0.20, or when 7.0 μm < D50 ≤ 8.0 μm, 0.15 ≤ FI ≤ 0.20.

[0041] In another aspect, the present invention relates to processes and materials defined by the provisions referenced below.

[0042] Clause 1. A process for producing a powdered positive electrode active material for a lithium ion secondary battery having particles containing Li, M, and O containing boron and tungsten, wherein M is: Co with a content x of 5.0 mol% or more and 35.00 mol% or less; Mn with a content y of 0 mol% or more and 35.00 mol% or less; Zr having a content m of 0 mol% or more and 2.00 mol% or less; B having a content b of 0.01 mol% or more and 2.00 mol% or less; W with a content c of 0.01 mol% or more and 2.00 mol% or less; a dopant A having a content z of 0 mol% or more and 2.00 mol% or less, comprising at least one element from the group consisting of Mg, Al, Nb, and Ti; (100-xymbc) mol% Ni content, the particles having a Li / M molar ratio of 0.98 or more and 1.10 or less, and the process comprises: mixing a Ni-based precursor, a Li source, and optionally sources of Zr and A to obtain a first mixture; sintering the first mixture at a first temperature of at least 700° C. and at most 1000° C. to obtain a first sintered body; A step of pulverizing the first sintered body to obtain a crushed powder; mixing the crushed powder with a boron source to obtain a second mixture; heat treating the second mixture at a second temperature of at least 300°C and at most 750°C, the process being characterized in that the tungsten source is milled together with the first sintered body to obtain a crushed powder comprising tungsten.

[0043] Within the framework of the first clause, the step of sintering the first mixture is defined as a step of heating the first mixture to produce a sintered body from the first mixture. The sintered body is thus a product resulting from the sintering process, which has a different chemical composition than that of the first mixture (i.e. before sintering).

[0044] Clause 2. The process of clause 1, wherein the tungsten source is a nanometer-sized powder, where nanometer-sized powder means a powder having W-based particles with a median particle size of less than 1 μm and equal to or greater than 1 nm.

[0045] Clause 3. The process of clause 2, wherein the tungsten source is WO3.

[0046] Clause 4. The process of any one of clauses 1 to 3, wherein the boron source is H3BO3.

[0047] Clause 5. The process of any one of clauses 1 to 4, wherein the Ni-based precursor is at least one compound selected from the group consisting of Ni-based oxide, Ni-based hydroxide, Ni-based carbonate, or Ni-based oxyhydroxide.

[0048] Clause 6. The process of any one of clauses 1 to 5, wherein the lithium source is at least one compound selected from the group consisting of Li2CO3, Li2CO3·H2O, LiOH, LiOH·H2O, or Li2O.

[0049] Clause 7. The process of any one of clauses 1-6, wherein the zirconium source is at least one compound selected from the group consisting of ZrO2, ZrO, ZrC, ZrN, Zr(OH)4, Zr(NO3)4, or ZrSiO4.

[0050] Clause 8. The process according to any of clauses 1 to 7, wherein the first sintering temperature is at least 700°C, preferably at least 800°C, more preferably at most 880°C.

[0051] Clause 9. The process of clause 8, wherein the second mixture is heat treated at a second temperature of at least 300°C, preferably at least 350°C, more preferably at most 400°C.

[0052] Clause 10. The process according to any one of clauses 1 to 9, wherein the tungsten source is added during the grinding step at a weight content of tungsten of 4000 ppm or more and 6000 ppm or less relative to the weight of the sintered body.

[0053] Clause 11: The process according to any one of clauses 1 to 10, wherein the crushed powder obtained in the milling step of the first sintered body has a median particle size D50 of at least 4.0 μm and at most 10.0 μm, more preferably at most 9.0 μm, even more preferably at most 8.0 μm.

[0054] Clause 12: The process according to any one of clauses 1 to 11, wherein the grinding step of the first sintered body is carried out in an air classifying mill.

[0055] Clause 13. A powdered positive electrode active material for a lithium ion secondary battery having particles containing Li, M, and O, wherein M is: Co with a content x of 5.0 mol% or more and 35.00 mol% or less; Mn with a content y of 0 mol% or more and 35.00 mol% or less; Zr having a content m of 0 mol% or more and 2.00 mol% or less; B having a content b of 0.01 mol% or more and 2.00 mol% or less; W with a content c of 0.01 mol% or more and 2.00 mol% or less; Contains at least one element selected from the group consisting of Mg, Al, Nb, and Ti; dopant A with a content z of 0 mol % or more and 2.00 mol % or less; and (100-xymbc) mol% Ni content, the particles having a Li / M molar ratio of 0.98 or greater and 1.10 or less, and the powdered positive electrode active material is characterized in that the particles have a w1 / (w1+w2) ratio of greater than 0.40 as measured by XANES, where w1 is the weight percent of Li2WO4 contained in the active material and w2 is the weight percent of WO3 contained in the active material.

[0056] Clause 14. The powdered positive electrode active material according to clause 13, wherein the molar ratio of Li2WO4(w1) to the total molar content of Li2WO4(w1) and WO3(w2) is at least 0.45, preferably at least 0.50, and more preferably at most 1.00.

[0057] Article 15. General formula: Li a Ni 1-x-y-m-z Co x Mn y Zr m B b W c A z O d 15. The powdered positive electrode active material of clause 13 or 14, comprising particles having the formula: wherein 0.99≦a≦1.10, 0.05≦x≦0.35, 0.00≦y≦0.35, 0.00≦m≦0.02, 0.0001≦z≦0.02, 0.0001≦b≦0.02, 0.0001≦c≦0.02, and 1.80≦d≦2.20.

[0058] Article 16. Particles: It belongs to the R-3m space group. General formula: Li a Ni 1-x-y-m-z CO x Mn y Zr m B b W c A z O d wherein 0.99≦a≦1.10, 0.05≦x≦0.35, 0.00≦y≦0.35, 0.00≦m≦0.02, 0.0001≦z≦0.02, 0.0001≦b≦0.02, 0.0001≦c≦0.02, and 1.80≦d≦2.20; A second phase having the general formula Li2WO4 and belonging to the R-3 space group, and 16. The powdered positive electrode active material according to any one of items 13 to 15, having a third phase having the general formula WO3 and belonging to the P21 / n space group.

[0059] Clause 17: The powdered positive electrode active material according to any one of clauses 13 to 16, having a median particle size D50 of at least 4.0 μm and at most 10.0 μm, more preferably at most 9.0 μm, and even more preferably at most 8.0 μm.

[0060] Clause 18. A powdered precursor mixture for producing a powdered positive electrode active material according to any one of clauses 13 to 17, wherein the precursor has particles containing Li, M, and O, and M is Co with a content x of 5.00 mol% or more and 35.00 mol% or less; Mn with a content y of 0 mol% or more and 35.00 mol% or less; Zr having a content m of 0 mol% or more and 2.00 mol% or less; W with a content c of 0.01 mol% or more and 2.00 mol% or less; Contains at least one element selected from the group consisting of Mg, Al, Nb, and Ti; dopant A with a content z of 0 mol % or more and 2.00 mol % or less; and (100-xymc) mol% Ni content, A powdered precursor compound, the particles having a Li / M molar ratio of 0.98 or more and 1.10 or less, the powdered precursor having a powder flowability of less than 0.20 and preferably greater than 0.10. [Brief description of the drawings]

[0061] [Figure 1] 1 is an image of a Powder Flow Tester (PFT). [Diagram 2] FIG. 1 is a schematic diagram of a trough as part of a PFT. [Diagram 3] 1 is a diagram of the preparation process of EX1.1 according to the present invention. [Figure 4] 1 is a diagram of the preparation process of EX2.1 according to the present invention. [Diagram 5] 1 is a diagram of the preparation process of EX2.1 according to the present invention. [Figure 6] 1 is a graph showing the relationship between D50 (x-axis) obtained from particle size distribution measurement and flow index FI (y-axis) of EX and CEX. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0062] In order to enable the practice of the invention, preferred embodiments are described in detail in the drawings and the following detailed description. Although the invention has been described with reference to these specific preferred embodiments, it will be understood that the invention is not limited to these preferred embodiments. On the contrary, however, the invention includes numerous alternatives, modifications and equivalents, as will become apparent from a consideration of the following detailed description and the accompanying drawings.

[0063] The invention is further illustrated in the following examples.

[0064] 1. Description of analysis method 1.1.Coin cell test 1.1.1. Preparation of Coin Cells In preparing the positive electrode, the positive electrode active material powder P, the conductor C (SuperP, Timcal (Imerys Graphite&Carbon), http: / / www.imerys-graphite-and-carbon.com / wordpress / wp-app / uploads / 2018 / 10 / ENSACO-150-210-240-250-260-350-360-G-ENSACO-150-250-P-SUPER-P-SUPER-P-Li-C-NERGY-SUPER-C-45-65-T_V-2.2-USA-SDS.pdf), binder B (KF#9305, Kureha, http: / / www.kureha.co.jp / en / business / material / pdf / KFpolyme_BD_en.pdf) in a weight ratio of P:C:B of 90:5:5, and solvent (NMP, Mitsubishi Chemical, https: / / www.m-chemical.co.jp / en / prod A slurry containing 1,2-dichlorophenyl ether (UCTs / departments / mcc / c4 / product / 1201005_7922.html) is prepared by using a high-speed homogenizer. The homogenized slurry is spread onto one side of an aluminum foil using a doctor blade coater with a gap of 230 μm. The slurry-coated foil is dried in an oven at 120° C. for 30 minutes and then pressed using a calendaring tool. The calendar-pressed slurry-coated foil is dried again in a vacuum oven for 12 hours to completely remove the residual solvent in the electrode film. The coin cell is assembled in an argon-filled glove box. A separator (Celgard® 2320, Arora, P. & Zhang, Z. (John) (2004) Battery Separators. Chemical Reviews, 104(10), 4419-4462) are placed between the positive electrode and a piece of lithium foil used as the negative electrode. 1M LiPF6 in EC:DMC (1:2 by volume) is used as the electrolyte and dropped between the separator and the electrode. The coin cell is then completely sealed to prevent electrolyte leakage.

[0065] Test Method Each coin cell is subjected to charge-discharge cycles at 25°C using a Toscat-3100 computer-controlled constant current charge-discharge cycling station (Toyo System, http: / / www.toyosystem.com / image / menu3 / toscat / TOSCAT-3100.pdf). The coin cell test procedure uses a current definition of 1C at 160mA / g and consists of the following three parts:

[0066] Part I is the rate performance evaluation of the cathode active material powders at 0.1C, 0.2C, 0.5C, 1C, 2C and 3C in the window range of 4.3-3.0V / Li metal. Except for the first cycle where the initial charge capacity (CQ1) and discharge capacity (DQ1) are measured in constant current mode (CC), all subsequent cycles are characterized by constant current constant voltage charging with the cut-off current as 0.05C. A rest time (between each charge and discharge) of 30 minutes is allowed for the first cycle and 10 minutes for all subsequent cycles.

[0067] The irreversible capacity IRRQ is expressed as a percentage as follows:

[0068]

number

[0069] Part II is the evaluation of cycle life at 1C. The charge cutoff voltage is set at 4.5V / Li metal. The discharge capacity at 4.5V / Li metal is measured at 0.1C in cycles 7 and 34, and at 1C in cycles 8 (DQ8) and 35 (DQ35). The first capacity fade, QF1C, is calculated as follows:

[0070]

number

[0071] Part III is the evaluation of cycle life at 1C (i.e., at a charge rate of 1C). The charge cutoff voltage is set at 4.5V / Li metal. The discharge capacity at 4.5V / Li metal is measured at 1C at cycles 36 and 60. The second capacity fade, QF1C1C, is calculated as follows:

[0072]

number

[0073] The table below summarises the three parts mentioned above.

[0074] [Table 1]

[0075] * "-" means that no end current is applied (i.e., the measurement is performed in constant current mode).

[0076] 1.3.Powder flowability test Powder flowability testing is performed on a Brookfield Powder Flow Tester (PFT) with Powder Flow Pro Software (Brookfield Engineering Laboratories, Inc., https: / / www.brookfieldengineering.com / product / powder-flow-testers / pft-powder-flow-testers).

[0077] The measurement test is performed in accordance with the standard test method described in pages 16-19 and 27-30 of the Brookfield Powder Flow Tester Operation Manual No. M09-1200-F1016 (https: / / www.brookfieldengineering.com / products / powder-flow-testers / - / media / b58fc1f1e4414d3a8e3b80683d5438e7.ashx).

[0078] A photograph of the PFT apparatus used to perform the PFT tests is shown in Figure 1. The apparatus includes a vane lid (circle 1) and a trough (circle 2). The trough has a 6 inch diameter with a volume of 230 cc, and the vane lid has a 6 inch diameter and a volume of 33 cc.

[0079] The test is carried out in accordance with the above standard test method as specified below.

[0080] Step a) The trough is cleaned with a pressurized air gun, weighed and then filled with the sample material.

[0081] Step b) Scoop the powder into a clean trough. This step b is followed by steps c-g.

[0082] Step c) Fixing the inner catch tray with shaping blades and outer catch tray to the trough. A schematic diagram of the (inner and outer) catch trays and troughs is shown in Figure 2. The inner and outer catch trays are provided to contain excess powder spillage from the powder deposited in the trough, which occurs during the shaping step (step d below cfr.).

[0083] Step d) Shaping the powder, which means distributing it evenly in the trough by rotating the shaping blade.

[0084] Step e) Remove the catch tray and then determine the weight of the powder of the sample material in the trough by subtracting the weight of the clean, empty trough from the weight of the trough filled with the shaped sample material powder.

[0085] Step f) The weight of the shaped sample material powder in the trough is entered into Brookfield Powder Flow Pro software (https: / / www.brookfieldengineering.com / products / software / powder-flow-pro) and the flowability test is initiated by performing sequential steps g)a through g)e.

[0086] Step g) The operation principle of the PFT (Figure 1) consists of the following: a. Drive the vane lid (reference number 1 in FIG. 1) vertically downward onto the powder sample contained in the trough (reference number 2 in FIG. 1). b. The trough is rotated with the rotational speed set at a prescribed axial speed of 1.0 mm / sec and torsional speed of 1.0 revolutions / hour, and the torque resistance of the powder in the trough moving against the powder in the stationary lid (number 2 in Figure 1) is measured by a calibrated reaction torque sensor. c. Five compression steps (also called the main consolidation stress σ1 expressed in KPa) are performed, each of which applies a certain intensity |σ1| (x-axis). In each of these compression steps, a certain torque (intensity |σ c |-y axis) is applied to the powder. This particular torque is the uniaxial fracture strength (σ c , expressed in KPa). d. Strength response σ to five different stresses σ1 applied to the powder c These responses are then recorded in a computer as σ1 (x-axis) versus σ according to the measurement results in Tables 2 to 9. c (y-axis) Plot on a curve.

[0087] CEX1:

[0088] [Table 2]

[0089] EX1.1:

[0090]

Table 3

[0091] EX1.2:

[0092]

Table 4

[0093] CEX2:

[0094]

Table 5

[0095] EX2.1:

[0096]

Table 6

[0097] EX2.2:

[0098]

Table 7

[0099] CEX3:

[0100]

Table 8

[0101] EX3.1:

[0102]

Table 9

[0103] EX3.2:

[0104]

Table 10

[0105] The flow index, FI, is calculated by linear fitting of the σ1 and σc responses plotted in (ec). The resulting linear equation is: CEX1:σ c = 0.38 × σ1 + 0.36, R = 0.995, EX1.1:σ c = 0.25 × σ1 + 0.19, R = 0.999, EX1.2:σ c = 0.20 × σ1 + 0.52, R = 0.998, CEX2:σ c = 0.28 × σ1 + 0.95, R = 0.991, EX2.1:σ c = 0.19 × σ1 + 0.29, R = 0.995, EX2.2:σ c = 0.16 × σ1 + 0.22, R = 0.994, CEX3:σ c = 0.25 × σ1 + 0.10, R = 0.995, EX3.1:σ c = 0.19 × σ1 + 0.34, R = 0.988, and EX3.2:σ c = 0.29 × σ1 + 0.37, R = 0.997.

[0106] σ c The slope of the fitted line, σ = slope × σ1 + coefficient, is the flow index and ranges from 0.0 to 1.0. As the FI approaches 0.0, the sample is more free-flowing. As the FI approaches 1.0, the sample is more cohesive. Flow index is unitless.

[0107] The R value is a correlation coefficient that indicates the strength of the linear relationship between the x and y variables. Its value ranges from 0 to 1, and an R value approaching 1 indicates a stronger linear relationship between the x and y variables. An R value equal to 1 implies a confirmed linear relationship between the x and y variables.

[0108] 1.5 particle size distribution The particle size distribution (psd) of water insoluble powders such as nickel-based transition metal oxyhydroxide powders is measured by dispersing each powder sample in aqueous media by using a Malvern Mastersizer3000 equipped with a Hydro MV wet dispersion accessory (https: / / www.malvernpananalytical.com / en / products / product-range / mastersizer-range / mastersizer-3000#overview). To improve the dispersion of the powder, sufficient ultrasonic irradiation and agitation are applied and appropriate surfactants are introduced.

[0109] The psd of water-soluble powders (such as H3BO3) is measured after dispersing the powder sample in air medium by using a Malvern Mastersizer3000 equipped with an Aero S dry dispersion accessory. D50 is defined as the particle size at 50% of the cumulative volume percent distribution obtained on the Malvern Mastersizer3000.

[0110] 2. Examples and Comparative Examples Example 1 Li 1.02 Ni 0.61 Mn 0.22 Co 0.17 A positive electrode active material powder comprising particles having a general formula of O2 and further containing Al-oxide on the surface of the particles is obtained based on a solid-state reaction between a lithium source and a transition metal-based source. The process diagram is shown in Figure 3 and is carried out as follows:

[0111] Step 1) Preparation of metal hydroxide precursor: General formula Ni 0.63 Mn 0.22 Co 0.15 Powders of nickel-based transition metal hydroxides with (OH)2 (TMH1) are prepared by a co-precipitation process in a large-scale continuous stirred tank reactor (CSTR) with mixed nickel manganese cobalt sulfate, sodium hydroxide, and ammonia.

[0112] Step 2) First Mixing: The powder of the transition metal hydroxide precursor TMH1 prepared in step 1) is mixed with Li2CO3 to obtain a first mixture having a lithium-to-metal molar ratio (Li / M) of 0.92.

[0113] Step 3) First firing: The first mixture of step 2) is fired at 900° C. for 10 hours in an air atmosphere to obtain a first fired body.

[0114] Step 4) Crushing and sieving: The first fired body of step 3) is crushed and sieved to produce a first crushed powder.

[0115] Step 5) Second Mixing: The first ground powder from step 4) is mixed with LiOH to produce a second mixture having a lithium to metal molar ratio (Li / M) of 1.05.

[0116] Step 6) Second firing: The second mixture of step 5) is sintered at 933° C. for 10 hours in an air atmosphere to produce a second fired body.

[0117] Step 7), crushing and sieving: The second fired body is crushed and sieved to produce a second crushed powder.

[0118] Step 8) Third Mixing: The second ground powder from step 7) is mixed with 0.19 mol% Al2O3, 3 mol% Co3O4, and 3 mol% LiOH, relative to the total molar content of Ni, Mn, and Co, to produce a third mixture.

[0119] Step 9) Third firing: The third mixture of step 8) is sintered at 775° C. for 12.3 hours in an air atmosphere to produce a third fired body.

[0120] Step 10) Grinding and sieving: The third sintered body (which is the agglomerated sintered body according to the present invention) is put into a grinding and sieving device such as an air classifier mill (ACM) together with Al2O3 nanopowder having 0.09 mol% relative to the total molar content of Ni, Mn, and Co (500 ppm Al relative to the total weight of the third sintered body) to be ground together with Al2O3 nanopowder to produce a third ground powder, which is a positive electrode active material powder containing 0.56 mol% Al, and is referred to as EX1.1.

[0121] EX1.1 is according to the present invention.

[0122] EX1.2 is prepared in the same way as EX1.1, except that the amount of Al2O3 nanopowder in step 10) is 0.19 mol% (1000 ppm Al relative to the total weight of the third fired body). EX1.2 contains 0.74 mol% Al relative to the total molar content of Ni, Mn, and Co.

[0123] EX1.2 is according to the present invention.

[0124] Comparative Example 1 CEX1 is obtained by the same method as EX1.1 except that no Al2O3 nanopowder is added during the grinding in step 10). CEX1 contains 0.37 mol% Al with respect to the total molar content of Ni, Mn, and Co.

[0125] CEX1 is not according to the present invention but according to WO'349.

[0126] Example 2 Li 1.075 Ni 0.34 Mn 0.32 Co 0.33 A positive electrode active material powder comprising particles having a general formula of O2 and further containing Al-oxide on the surface of the particles is obtained based on a solid-state reaction between a lithium source and a transition metal-based source. The process diagram is shown in Figure 4 and is carried out as follows:

[0127] Step 1) Preparation of metal hydroxide precursors: Two separate batches of nickel-based transition metal hydroxide powders, characterized by two different particle sizes, are prepared by a co-precipitation process in a large-scale continuous stirred tank reactor (CSTR) containing a mixture of nickel manganese cobalt sulfate, sodium hydroxide, and ammonia. The products from the two batches have the same general formula Ni 0.342 Mn 0.326 Co 0.332 (OH)2 but with two different average particle sizes (D50) of 3 μm (TMH2) and 10 μm (TMH3).

[0128] Step 2) First mixing: Each of the transition metal hydroxide precursors TMH2 and TMH3 powders prepared in step 1) is mixed with Li2CO3 to obtain a first mixture, in which the mixing ratio of TMH2 and TMH3 powders is 30 wt%:70 wt%, and the lithium to metal molar ratio (Li / M) is 1.10.

[0129] Step 3) First firing: The first mixture of step 2) is fired at 720° C. for 2 hours in an air atmosphere to obtain a first fired body.

[0130] Step 4) Crushing and sieving: The first fired body of step 3) is crushed and sieved to produce a first crushed powder.

[0131] Step 5) Second firing: The first pulverized powder of step 4) is fired at 985° C. for 10 hours in an air atmosphere to produce a second fired body.

[0132] Step 6) Grinding and sieving: The second sintered body (which is the agglomerated sintered body according to the present invention) is placed in a grinding and sieving device such as ACM together with Al2O3 nanopowder having 0.46 mol% relative to the total molar content of Ni, Mn, and Co (2500 ppm Al relative to the total weight of the third sintered body) and ground together with the Al2O3 nanopowder to produce a second ground powder, which is a cathode active material powder containing 0.93 mol% Al, and is designated as EX2.1.

[0133] EX2.1 is according to the present invention.

[0134] EX2.2 is prepared in the same manner as EX2.1, except that SiO2 nanopowder is used in step 6). EX2.2 contains 0.89 mol% Si with respect to the total molar content of Ni, Mn, and Co.

[0135] EX2.2 is according to the present invention.

[0136] Comparative Example 2 CEX2 is obtained by the same method as EX2.1 except that no Al2O3 nanopowder is added during grinding in step 6).

[0137] CEX2 is not according to the present invention but according to WO'349.

[0138] Example 3 Li 1.06 Ni 0.65 Mn 0.20 Co 0.15 Zr 0.00 The NMC powder, which has a general formula of O2 and contains particles containing W-oxide and B-oxide on their surface, is obtained based on the solid-state reaction between a lithium source and a transition metal-based source. The process diagram is shown in Figure 5 and is carried out as follows:

[0139] Step 1) Preparation of metal oxide precursors: Coprecipitation Two separate batches of nickel-based transition metal oxyhydroxide powders, characterized by two different particle sizes, are prepared by a coprecipitation process in a large-scale continuous stirred tank reactor (CSTR) containing a mixture of nickel manganese cobalt sulfate, sodium hydroxide, and ammonia. The products from the two batches have the same general formula Ni 0.65 Mn 0.20 Co 0.15 (OH)2 but with two different average particle sizes (D50) of 9.5 μm (TMH3) and 4.5 μm (TMH4), respectively. b. Heat treatmentTMH3 was placed on an alumina tray and heated at 425°C for 7 hours under dry air flow to produce oxide precursor powder, designated TMO1. TMH4 was separately heat treated according to the same method as THM3 to produce oxide precursor powder, designated TMO2.

[0140] Step 2) First Mixing: Each of the transition metal oxide precursors TMO1 and TMO2 powders prepared in step 1) is mixed with LiOH and ZrO2 powders to obtain a first mixture. The TMO1 and TMO2 powders are mixed in a weight ratio of 7:3, the lithium to metal molar ratio is 1.03, and the Zr content in the mixture is 3700 ppm.

[0141] Step 3) First firing: The first mixture of step 2) is sintered at 855° C. for 12 hours in an oxygen-containing atmosphere to obtain a first fired body.

[0142] Step 4) Grinding and sieving: During the grinding and sieving process, the first sintered body (which is the agglomerated sintered body according to the present invention) is mixed with WO3 nanopowder (median particle size D50 of 0.18 μm). The product from this grinding and sieving process is a first ground powder containing 4500 ppm W, designated EX3.1, which is an intermediate powdered positive electrode active material that is converted to the final powdered positive electrode active material product EX3.2 obtained from the processing of EX3.1 in steps 5 and 6).

[0143] Step 5) Second Mixing: EX3.1 from step 4) is mixed with H3BO3 powder with D50 of 4.8 μm to obtain a second mixture containing 500 ppm B.

[0144] Step 6) Second sintering: The second mixture of step 5) is sintered at 385°C for 8 hours under oxygen atmosphere to obtain a second sintered body. The second sintered body is crushed and sieved by air classifier mill (ACM) to obtain the positive electrode active material, which is EX3.2 material.

[0145] EX3.1 is according to the present invention.

[0146] Comparative Example 3 CEX3 is obtained by the same method as EX3.1 except that WO3 powder is added together with H3BO3 powder in step 5) instead of step 4).

[0147] CEX3 is not according to the present invention but according to WO'349.

[0148] The flowability test according to the method in section 1.3 is applied to the examples and comparative examples. The FI obtained for EX1.1, EX1.2, and CEX1 are 0.25, 0.20, and 0.38, respectively.

[0149] These results show that the fluidity of EX1.1 is significantly improved compared to CEX1 by the addition of Al2O3 nanopowder in step 10). The amount of excess Al2O3 nanopowder in EX1.2 slightly decreases the FI of the powder compared to EX1.1.

[0150] The fluxes obtained for EX2.1, EX2.2, and CEX2 are 0.19, 0.16, and 0.34, respectively.

[0151] These results show that the liquidity of EX2.1 is It shows that the addition of Al2O3 in the grinding step 6) significantly improves the flowability compared to CEX2. Improvement in flowability was also seen with the addition of SiO2 nanopowder in the grinding step 6) (cfr.EX2.2).

[0152] The FIs obtained for EX3.1, EX3.2, and EX3.3 are 0.19, 0.29, and 0.25, respectively.

[0153] These results indicate that the fluidity of EX3.1 is significantly improved by the addition of WO3 in step 4) compared to CEX3.

[0154] As a conclusion, a lower FI value indicates easier free-flowing characteristics of the powder, which is the objective of the present invention.

[0155] Figure 6 shows the D50 of the examples and comparative examples together with their corresponding FIs. In fact, as described above, powders having an FI of 0.10 to 0.30 are obtained at a D50 of 4 μm or more and 6 μm or less as shown by EX1.1 and EX1.2, and an FI of 0.10 to 0.22 is realized at a D50 of more than 6 μm and 8 μm or less as shown by EX2.1, EX2.2, and EX3.1. For example, when 4.0 μm ≤ D50 ≤ 6.0 μm and FI is 0.10 to 0.30, and when 6.0 μm < D50 ≤ 8.0 μm and FI is 0.10 to 0.22, it can be easily and thus quickly transported through the channels of the powder transport line to a milling (grinding) device such as an ACM.

[0156] According to the results of the aforementioned powder fluidity test, the addition of Al, Si, or W nano-powders during grinding has the advantage of reducing the FI of the powder and improving the powder free-flowing characteristics of the positive electrode active material powder.

[0157] Table 10 shows the results of the coin cell tests of the cathode material powders according to the examples and comparative examples. From this table, it is clear that EX1.1 and EX1.2 have better electrochemical performance compared to those obtained with CEX1, as shown by higher DQ1, lower IRRQ, and more stable attenuation rates indicated by lower QF1C and QF1C1C values.

[0158] EX2.1 and EX2.2 have electrochemical characteristics equivalent to those of CEX2 respectively, regardless of the addition of electrochemically inactive materials such as Ai2O3 or SiO2. Therefore, the present invention, which aims to obtain a positive electrode active material powder with improved fluidity, is achieved without sacrificing its electrochemical performance.

[0159]

Table 11

[0160] * A is added during the process of pulverizing the agglomerated fired body. ** A's Li a Ni b Co c Mn d D e O f A g O h The general formula of the type A refers to the composition of the active material particles A oxide particles mixed with the active material powder during the grinding step of the process according to the present invention. *** -: No data

Claims

1. A process for producing a powdered active cathode material for a lithium ion battery having particles including Li, M, and O, wherein M is: Co with a content x of 5.0 mol% or more and 40.00 mol% or less; Mn with a content y of 5.0 mol% or more and 40.00 mol% or less; A having a content c of 0.01 mol % or more and 2.00 mol % or less, containing at least one element from the group consisting of at least one element of W, Al, and Si; D having a content z of 0 mol% or more and 2.00 mol% or less, containing at least one element from the group consisting of Mg, Nb, Zr, B, and Ti; and (100-x-y-c-z) mol% Ni content; the particles having a Li / M molar ratio of 0.98 or greater and 1.10 or less, and the process further comprising: Preparing a powder mixture comprising a lithium source, a nickel source, a cobalt source, a manganese source, and optionally a D source; sintering the powder mixture at a temperature of at least 300° C. and at most 1000° C. to obtain an agglomerated sintered body; 11. A process comprising the steps of: grinding the agglomerated sintered body to obtain a crushed powder, the process being characterized in that a source of at least one of W, Al, and Si is ground together with the agglomerated sintered body, the source of at least one of W, Al, and Si being an oxide of at least one of W, Al, and Si.

2. 2. The process of claim 1, wherein the crushed powder obtained in the step of crushing the agglomerated sintered body has a median particle size D50 of at least 4.0 μm and at most 10.0 μm.

3. 3. The process of claim 1 or 2, wherein the step of comminuting the agglomerated calcined body is carried out in an air classifying mill.

4. 4. The process according to any one of claims 1 to 3, wherein the source of at least one of the elements W, Al and Si is a nanometer sized oxide powder and is added after the calcination step to obtain the agglomerated calcined body.

5. A comprises Al, and the Al source is Al 2 O 3 The process according to any one of claims 1 to 4, wherein

6. 6. The process of claim 5, wherein the Al source is added in a grinding step in an amount equal to a molar content of Al of 0.08 mol % or more and 1.50 mol % or less relative to the sum of the molar contents of Ni, Mn, and Co in the agglomerated sintered body.

7. A contains Si, and the Si source is SiO 2 The process according to any one of claims 1 to 6, wherein

8. 8. The process of claim 7, wherein the Si source is added in a grinding step in an amount equal to a molar content of Si of 0.36 mol % or more and 1.45 mol % or less, relative to the total molar content of Ni, Mn, and Co in the agglomerated sintered body.

9. A contains W, and the W source is WO 3 The process according to any one of claims 1 to 8, wherein

10. 10. The process of claim 9, wherein the W source is added in a grinding step in an amount equal to a molar content of W equal to or greater than 0.20 mol % and equal to or less than 0.35 mol % relative to the sum of the molar contents of Ni, Mn, and Co in the agglomerated sintered body.

11. The lithium source is Li 2 CO 3 , Li 2 CO 3 ・H 2 O, LiOH, LiOH・H 2 O or Li 2 The process of any one of claims 1 to 10, wherein the compound is at least one compound selected from the group consisting of O.

12. The process of any one of claims 1 to 11, wherein the crushed powder is a powdered positive electrode active material.

13. 5 mol%≦x≦35 mol% and 5 mol%≦y≦35 mol%, M contains B having a content b of 0.01 mol % or more and 2.00 mol % or less, M contains W in an amount of 0.01 mol % or more and 2.00 mol % or less, M contains Zr in a content m of 0 mol% or more and 1.99 mol% or less, The step of preparing a powder mixture comprises mixing a Ni-based precursor, a Li source, and optionally sources of Zr and A to obtain a first mixture; In the step of sintering the powder mixture, the first mixture is the powder mixture, and the first mixture is sintered at a first temperature of at least 700° C. to obtain a first sintered body; In the step of pulverizing the aggregated sintered body, the aggregated sintered body is the first sintered body, and a W supply source is pulverized together with the aggregated sintered body to obtain a crushed powder containing W, the process includes mixing the crushed powder with a B-source to obtain a second mixture; The process of any one of claims 1 to 11, wherein the process comprises heat treating the second mixture to a second temperature of at least 300°C and at most 750°C.

14. A powdered material having particles comprising Li, M, and O, wherein M is Co with a content x of 5.0 mol% or more and 40.00 mol% or less; Mn with a content y of 5.0 mol% or more and 40.00 mol% or less; A having a content c of 0.01 mol % or more and 2.00 mol % or less, containing at least one element from the group consisting of W, Al, and Si; D having a content z of 0 mol% or more and 2.00 mol% or less, containing at least one element from the group consisting of Mg, Nb, Zr, B and Ti; and (100-x-y-c-z) mol% Ni content; the particles have a Li / M molar ratio of 0.98 or more and 1.10 or less; The particles have an oxide of at least one of W, Al, and Si on a surface of the particles; the powdered material is a positive electrode active material for a lithium ion battery; the powdered material has a powder flowability of at most 0.30; The flow rate is 230 cm 3 The slope of the line fitted to experimental results of uniaxial fracture strength measured in a 6-inch diameter annular shear cell having a volume of 0.01 mm and at several principal consolidation stresses for powdered materials.

15. the powdered material having a D50 of at least 4.0 μm and at most 10.0 μm; The powdered material has a D50 of at least 4.0 μm and at most 6.0 μm, the powdered material having a flowability of at least 0.10 and at most 0.30; 15. The powdered material of claim 14, wherein the D50 is the median particle size of the powdered material.

16. the powdered material having a D50 of at least 4.0 μm and at most 10.0 μm; The powdered material has a D50 of more than 6.0 μm and a maximum of 10.0 μm, the powdered material having a flowability of at least 0.10 and a maximum of 0.225; 15. The powdered material of claim 14, wherein the D50 is the median particle size of the powdered material.

17. 17. The powdered material according to any one of claims 14 to 16, wherein the powdered material has a D50 of more than 6.0 μm and a maximum of 10.0 μm and a flowability of at least 0.10 and a maximum of 0.20, or the powdered material has a D50 of at least 4.0 μm and a maximum of 6.0 μm and a flowability of at least 0.10 and a maximum of 0.30, D50 being the median particle size of the powdered material.

Citation Information

Patent Citations

  • Monocrystal-like lithium nickel cobalt manganese composite oxide material and preparation method thereof

    CN110265657A

  • Lithium transition metal based compound powder, manufacturing method thereof, spray drying body used as calcination precursor thereof, and positive electrode for lithium secondary battery using the powder, and lithium secondary battery

    JP2008270161A

  • Lithium transition-metal compound powder, its manufacturing method, spray drying object acquired during spray drying process, positive electrode for lithium secondary battery using it, and lithium secondary battery

    JP2009081130A

  • Positive electrode composition for nonaqueous electrolyte secondary battery

    JP2013239434A

  • Nickel-based active material for lithium secondary battery, method of preparing the same, and lithium secondary battery including positive electrode including the same

    JP2018014326A